Hazy Blue Worlds: A Holistic Aerosol Model for Uranus and Neptune, Including Dark Spots. Issue 6 (4th June 2022) - Irwin, P. G. J.; Teanby, N. A.; Fletcher, L. N.; Toledo, D.; Orton, G. S.; Wong, M. H.; Roman, M. T.; Pérez‐Hoyos, S.; James, A.; Dobinson, J.
Abstract: We present a reanalysis (using the Minnaert limb‐darkening approximation) of visible/near‐infrared (0.3–2.5 μm) observations of Uranus and Neptune made by several instruments. We find a common model of the vertical aerosol distribution i.e., consistent with the observed reflectivity spectra of both planets, consisting of: (a) a deep aerosol layer with a base pressure >5–7 bar, assumed to be composed of a mixture of H2 S ice and photochemical haze; (b) a layer of photochemical haze/ice, coincident with a layer of high static stability at the methane condensation level at 1–2 bar; and (c) an extended layer of photochemical haze, likely mostly of the same composition as the 1–2‐bar layer, extending from this level up through to the stratosphere, where the photochemical haze particles are thought to be produced. For Neptune, we find that we also need to add a thin layer of micron‐sized methane ice particles at ∼0.2 bar to explain the enhanced reflection at longer methane‐absorbing wavelengths. We suggest that methane condensing onto the haze particles at the base of the 1–2‐bar aerosol layer forms ice/haze particles that grow very quickly to large size and immediately "snow out" (as predicted by Carlson et al. (1988), https://doi.org/10.1175/1520-0469(1988)045<2066:CMOTGP>2.0.CO;2 ), re‐evaporating at deeper levels to release their core haze particles to act as condensation nuclei for H2 S ice formation. In addition, we find that the spectral characteristics of "dark spots", such as the Voyager‐2/ISS Great Dark Spot and the HST/WFC3 NDS‐2018, are well modelled by a darkening or possibly clearing of the deep aerosol layer only. Plain Language Summary: Previous studies of the reflectance spectra of Uranus and Neptune have concentrated on individual, narrow wavelength regions and the conclusions have been difficult to compare with each other. Here, we analyse a combined set of observations from three different instruments covering the wavelength range 0.3–2.5 μm to arrive at a single aerosol model that matches the observations at all wavelengths simultaneously for both planets. We conclude that photochemical haze produced in the upper atmospheres of both planets is steadily mixed down to lower layers, where it forms part of a vertically thin layer in a statically stable region above the methane condensation level at 1–2 bar. We suggest that methane condenses so rapidly upon these haze particles that it efficiently "snows" out at the base of this layer, falling to lower, warmer levels, where the methane evaporates, releasing the core haze particles to "seed" H2 S condensation. For Neptune we need to add an additional layer of moderately large methane ice particles at ∼0.2 bar. Intriguingly, we find that a darkening (or perhaps clearing) of the lowest H2 S/haze layer matches very well the observed properties of the dark spots seen occasionally in Neptune's atmosphere and very occasionally in Uranus's atmosphere. Key Points: Ice Giant reflectivity spectra from 0.3 to 2.5 μm well approximated by a single aerosol model comprised of three to four distinct layers Static stability region at 1–2 bar, caused by methane condensation, seems to lead to build‐up of haze and seeds CH4 snow at its base Darkening of deepest H2 S/haze layer, based at p > 5–7 bar, found to account well for spectral properties of dark spots